Brief Report: Impaired Cell Reprogramming in Nonhomologous End Joining Deficient Cells1. (23rd August 2013) - Molina‐Estevez, F. Javier; Lozano, M. Luz; Navarro, Susana; Torres, Yaima; Grabundzija, Ivana; Ivics, Zoltan; Samper, Enrique; Bueren, Juan A.; Guenechea, Guillermo
Abstract: Although there is an increasing interest in defining the role of DNA damage response mechanisms in cell reprogramming, the relevance of proteins participating in nonhomologous end joining (NHEJ), a major mechanism of DNA double‐strand breaks repair, in this process remains to be investigated. Herein, we present data related to the reprogramming of primary mouse embryonic fibroblasts (MEF) from severe combined immunodeficient (Scid) mice defective in DNA‐PKcs, a key protein for NHEJ. Reduced numbers of induced pluripotent stem cell (iPSC) colonies were generated from Scid cells using reprogramming lentiviral vectors (LV), being the reprogramming efficiency fourfold to sevenfold lower than that observed in wt cells. Moreover, these Scid iPSC‐like clones were prematurely lost or differentiated spontaneously. While the Scid mutation neither reduce the proliferation rate nor the transduction efficacy of fibroblasts transduced with reprogramming LV, both the expression of SA‐β‐Gal and of P16/INK 4a senescence markers were highly increased in Scid versus wt MEFs during the reprogramming process, accounting for the reduced reprogramming efficacy of Scid MEFs. The use of improved Sleeping Beauty transposon/transposase systems allowed us, however, to isolate DNA‐PKcs‐deficient iPSCs which preserved their parental genotype and hypersensitivity to ionizing radiation. This new disease‐specific iPSC model would be useful to understand the physiological consequences of the DNA‐PKcs mutation during development and would help to improve current cell and gene therapy strategies for the disease. STEM Cells 2013;31:1726–1730